The Role of Gli1+ Mesenchymal Stem Cells in Osteogenesis of Craniofacial Bone - Laidi Wu; Zhixin Liu; Li Xiao; Mi Ai; Yingguang Cao; Jing Mao; Ke Song (Biomolecules, 2023)
Glioma-associated oncogene homolog 1 (Gli1) is a transcriptional activator of hedgehog (Hh) signaling that regulates target gene expression and several cellular biological processes. Cell lineage tracing techniques have highlighted Gli1 as an ideal marker for mesenchymal stem cells (MSCs) in vivo. Gli1+ MSCs are critical for the osteogenesis of the craniofacial bone; however, the regulatory mechanism by which Gli1+ MSCs mediate the bone development and tissue regeneration of craniofacial bone has not been systematically outlined. This review comprehensively elucidates the specific roles of Gli1+ MSCs in craniofacial bone osteogenesis. In addition to governing craniofacial bone development, Gli1+ MSCs are associated with the tissue repair of craniofacial bone under pathological conditions. Gli1+ MSCs promote intramembranous and endochondral ossification of the craniofacial bones, and assist the osteogenesis of the craniofacial bone by improving angiopoiesis. This review summarizes the novel role of Gli1+ MSCs in bone development and tissue repair in craniofacial bones, which offers new insights into bone regeneration therapy.